Smart Cards, Tokens, Security and Applications - Mayes, Keith; Markantonakis, Konstantinos (Springer US : Imprint: Springer, 2008)
Smart Cards, Tokens, Security and Applications provides a broad overview of the many card systems and solutions that are in practical use today. This state-of-the art work is written by contributing authors who are active researchers and acknowledged experts in their field. A single book cannot be found to match both the breadth and depth of content. This book combines a cross-discipline overview of smart cards, tokens and related security and applications plus a technical reference to support further research and study. A step-by-step approach educates the reader in card types, production, operating systems, commercial applications, new technologies, security design, attacks, application development, deployment and lifecycle management. By the end of the book the reader should be able to play an educated role in a smart card related project, even to programming a card application. Smart Cards, Tokens, Security and Applications is designed for a professional audience of practitioners and researchers.